Integrating Understanding by Design (UbD) into Elementary Science Learning: A Study on Teacher and Student Responses - Suryana, Sabila Idzni; Reizal, Haidhar; Sobari, Teti (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2025)
Understanding by Design (UbD) is a learning activity that focuses on the desired learning objectives. The purpose of this study was to determine the responses of elementary school teachers and students regarding the application of UbD to science learning in elementary schools. This study was conducted using a descriptive qualitative method using questionnaires and interview sheets involving 3 teachers and 52 elementary school students in several areas in Java. This study was conducted on science material in elementary schools. Data collection was carried out using a questionnaire referring to the Likert scale and interviews. The results showed that teachers and students gave a positive response to the application of UbD-based learning in elementary school science material. The average value of the teacher's response, which was 76.62, was in the good category. The average value of the student's response, which was 75.92, was also in the good category. UbD-based learning can make it easier for teachers to plan learning, structure learning activities well, and motivate students to learn and understand science material more easily, resulting in increased student learning outcomes.elitian ini untuk mengetahui tanggapan dari guru dan peserta didik sekolah dasar mengenai penerapan UbD pada pembelajaran IPA di sekolah dasar. Penelitian ini dilakukan dengan metode kualititatif deskriptif dengan melibatkan 3 guru dan 52 peserta didik sekolah dasar di beberapa daerah di Pulau Jawa. Penelitian ini dilakukan pada materi IPA di sekolah dasar. Pengumpulan data dilakukan dengan menggunakan angket yang mengacu pada skala Likert dan wawancara. Hasil penelitian menunjukkan bahwa guru dan siswa memberikan respon positif pada penerapaan pembelajaran berbasis UbD pada materi IPA sekolah dasar. Nilai rata-rata dari repon guru, yaitu sebesar 76,62 masuk pada kategori baik. Untuk nilai rata-rata dari respon peserta didik, yaitu sebesar 75,92 juga masuk pada kategori baik. Pembelajaran berbasis UbD dapat membuat guru lebih mudah dalam merencanakan pembelajaran, kegiatan pembelajaran testruktur dengan baik, dan membuat peserta didik termotivasi untuk belajar serta lebih mudah memahami materi IPA yang berakibat terjadinya peningkatan hasil belajar peserta didik.